Robust vibration control of wind-excited highrise building structures - Wang, Nengmou; Adeli, Hojjat (Journal of Civil Engineering and Management, 2015)
A robust filtered sliding mode control (SMC) approach is presented for vibration control of wind-excited highrise building structures. Rather than using a Lyapunov-function based control design, an alternative way is provided to find the control force based on the equivalent control force principle to obtain the control force. A low pass filter is properly selected to remove the high-frequency components of the control force while retaining the structural stability. The performance of the proposed filtered SMC is evaluated by application to a wind-excited 76-story building benchmark problem equipped with an active tuned mass damper (ATMD) on the roof. Due to the elimination of high-frequency part of the control force, the structure, sensors, actuators, and dampers are all less excited, and consequently their response is reduced compared with the unfiltered SMC approach. In addition, the required control forces are reduced which means a reduction in the size of actuators, thus making their implementation more practical. It is shown the proposed method is more robust to structural stiffness uncertainties compared with the linear quadratic Gaussian (LQG) algorithm and another implementation of SMC.